REMEDIASI MISKONSEPSI SISWA PADA MATERI GETARAN MENGGUNAKAN MODEL STAD BERBANTUAN WORD SQUARE - Titin, Irena; S, Stepanus Sahala; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aims of this research are to know influence cooperative learning model type student teams achievement divisions (STAD) helped word square to remediate student’  misconception in VIII level SMP Negeri 16 Pontianak on oscillation material. The shape of research is pre-experimental design with one group pretest-posttest design. The sample choosed using random with intact group technique so it was selected class VIII J academic year 2014/2015 numbered 26 students. The data instrument of this research is multiple choices with open reasons. The result of data analysis shown students’ misconception in pre-test is 96,15% and students’ misconception in post-test is 54,32%. So that, there is a decline students’ misconception is 42%. Based on the results of correlation test using Sperman-Rank test obtained  count (0,907) more than  table (0,392) on 26 students.  Beside that,  count (0,875) more than  table (0,738) on 8 sample. Thus, it can be cocluded that is significant correlation between concept understanding and misconception reduction on oscillation material in VIII level SMP Negeri 16 Pontianak. So, hopefully this research can be an alternative for teacher in learning or to remediate students’ misconception at school.Keywords:           Remediate misconceptions, oscillation, student teams achievement divisons (STAD), word square